Inclusion of alkylparabens in cyclodextrins - De Vries, Elise Janine Christl (University of Cape Town, 2014)
Includes bibliographical references. === The aim of this thesis was to prepare crystalline inclusion complexes with cyclodextrins (CDs), as hosts, and drugs, as guests, characterise them using various methods and attempt to elucidate their structures by X-ray diffraction methods to establish the detailed mode of drug inclusion in the solid state. Cyclodextrins and their derivatives have a low polarity central void formed by linked glucose residues of varying numbers. This annular cavity is able to encapsualte low molecular weight molecules and is therefore responsible for the great interest in CDs in host-guest chemistry. In addition, inclusion of drug molecules in cyclodextrins can significantly improve aspects of their performance, such as increased aqueous solubility and dissolution rates which lead to their increasing application in the pharmaceutical industry.